Abraham Maslow's hierarchy of human needs building self-actualization reflected in a Broken Home child character - Ulaya Ahdiani; Alfian Maulana (Universitas Ahmad Dahlan, 2023)
In the world where a broken family can breaks someone’s life, can self-actualization bring a better life to broken home children? Claire Legrand’s Some Kind of Happiness tells us about Finley Hart, an eleven years old child, who visits her estranged grandparents because her parents have problems leading to divorce. With a lot of mental problems faced by the character, this study wants to analyze how four basic needs build self-actualization. researcher collects the data from character Finley Hart in the novel Some Kind of Happiness with general inductive approach. This method enables researcher to dig significant data about Finley’s psychology over general condition in the story. Researcher also uses hierarchy of human needs theory by Abraham Maslow. This theory provides a structural explanation about basic human needs, self-actualization, and its benefit. From the study, researcher finds that every basic needs are important and supports each other in order to bring self-actualization. Self-actualization itself is crucial for it bring contentment to oneself. With the benefit of self-actualization, Finley has become a better and happier person. It proves that basic needs and self-actualization are essential for broken-home children.